1) 25 * 24 = 25 * (4*6) = (5*5) * (2*3*2*2) = 5*2*2*5*2*3 = 600;
2) 600 / 24 = 600 / (6*4) = (3*2*5*2*5*2)/(3*2*2*2) = (5*5) = 25;
3) 600 / 25 = 600 / (5*5) = (3*2*5*2*5*2)/(5*5) = (3*2*2*2) = 24;
14.7:0.6= 14.1 0.008т=8.000
1) y'= Cos(x⁷ - 2x) * (x⁷ - 2x)' + 8^Cosx*ln8 *(Cosx)' =
=(7x⁶ -2)Cos(x⁷ -2x) - 8^Cosx *ln8*Sinx
2) y' =20(x⁷ -9x)³ * (x⁷ - 9x)' = 20(x⁷ -9x)³ * (7x⁶ -9)
3) y = ln(6x -x⁸)*Ctg(eˣ +3)
Производную ищем по формуле: (UV)' = U'V + UV'
y' = ln'(6x -x⁸)*Ctg(eˣ +3) + ln(6x -x⁸)*Ctg'(eˣ +3)=
=1/(6х - х⁸)*(6 - 8х⁷)*Сtg(eˣ +3) - ln(6x -x⁸) * 1/Sin²(eˣ +3) * eˣ=
=(6 - 8х⁷)*Сtg(eˣ +3) / (6x -x⁸) - eˣln(6x -x⁸)/Sin²(eˣ +3)
Сам решай мозгов больше будет